Triple-zero singularity of a Kaldor–Kalecki model of business cycles with delay - Wu, Xiaoqin P. P. (Nonlinear Analysis: Modelling and Control, 2013)
In this manuscript, we study triple zero singularity of a Kaldor–Kalecki model of business cycles with delay in both the gross product and the capital stock. By using the frameworks of Campbell–Yuan [1] and Faria–Magalhães [2, 3], the normal form on the center manifold is derived for this singularity and hence the corresponding bifurcation diagrams such as Hopf, BT, zero-Hopf, and homoclinic bifurcations are obtained. An example is given to verify some theoretical results.